Effects of methylglyoxal and glyoxalase I inhibition on breast cancer cells proliferation, invasion, and apoptosis through modulation of MAPKs, MMP9, and Bcl-2. Issue 2 (1st February 2016) - Guo, Yi; Zhang, Yuning; Yang, Xunjun; Lu, Panpan; Yan, Xijuan; Xiao, Fanglan; Zhou, Huaibin; Wen, Chaowei; Shi, Mengru; Lu, Jianxin; Meng, Qing H.
Abstract: Emerging evidence indicates that methylglyoxal (MG) can inhibit tumorigenesis. Glyoxalase I (GLOI), a MG degradation enzyme, is implicated in the progression of human malignancies. However, little is known about the roles of MG and GLOI in breast cancer. Our purpose was to investigate the anticancer effects of MG and inhibition of GLOI on breast cancer cells and the underlying mechanisms of these effects. Our findings demonstrate that cell viability, migration, invasion, colony formation, and tubule formation were significantly restrained by addition of MG or inhibition of GLOI, while apoptosis was significantly increased. Furthermore, the expression of p-JNK, p-ERK, and p-p38 was markedly upregulated by addition of MG or inhibition of GLOI, whereas MMP-9 and Bcl-2 expression levels were dramatically decreased. These effects were augmented by combined treatment with MG and inhibition of GLOI. Collectively, these data indicate that MG or inhibition of GLOI induces anticancer effects in breast cancer cells and that these effects are potentiated by combination of the 2. These effects were modulated by activation of the MAPK family and downregulation of Bcl-2 and MMP-9. These findings may provide a new approach for the treatment of breast cancer.